A synopsis of Amischotolype (Commelinaceae) in Thailand, with a new record, A. gracilis - Boonsuk, Boonchuang; Kantachot, Chortip; Chantaranothai, Pranom (Phytotaxa, 2025)
A synopsis of the genus Amischotolype (Commelinaceae) in Thailand is presented. Thirteen species are enumerated, one of which, A. gracilis is a new record for Thailand. A lectotype is designated for A. welzeniana. An identification key to the Thai species of Amischotolype is provided, as well as notes on their ecology, distribution, vernacular names, specimens examined in Thailand, are cited.